The effects of the chemical composition on the structural, thermodynamic, and mechanical properties of all-inorganic halide perovskites. Issue 16 (8th July 2021) - Sánchez-Palencia, Pablo; García, Gregorio; Wahnón, Perla; Palacios, Pablo
Abstract : A systematic ab-initio study of all-inorganic perovskites with formula CsPb1− b Sn b (I1− x Br x )3  has been performed, elucidating the connection of that composition with their structural, thermodynamics and mechanical properties. Abstract : Organic–inorganic hybrid halide perovskites are widely used in optoelectronic devices, such as solar cells and light-emitting devices. Pursuing solutions to overcome the key problem of instability shown by most used MAPbI3 materials, all-inorganic perovskites like CsPbI3 are attracting considerable attention. Unfortunately, CsPbI3 still suffers from significant issues relating to chemical instability and toxicity due to the presence of Pb atoms; therefore, it is necessary to carry out a profound review of the properties of all-inorganic perovskites to overcome these problems. Experimental laboratories cannot afford, in terms of money and time, to synthesize and characterize large numbers of compounds to rigorously assess the outcomes. Therefore, a systematic density functional theory study of the family of all-inorganic perovskites with the general formula CsPb1− b Sn b (I1− x Br x )3 has been performed, covering the entire chemical composition range and elucidating the connections between composition and the structural, thermodynamic, and mechanical properties, in addition to any effects on stability. Our results allow us to gain significant insight in the search for new all-inorganic perovskites with tailored structural, thermodynamic, and mechanical properties via fine-tuning the chemical composition.